The Influence of Entrepreneurship Education on Entrepreneurial Intention with Industrial Work Practice as a Mediating Variable among Vocational School Students in Jakarta - Aliyah, Ulfatul; Suparno, Suparno; Pratama, Aditya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine: (1) the effect of entrepreneurship education on entrepreneurial intentions among vocational high school students in Jakarta, (2) the effect of industrial work experience on entrepreneurial intentions among vocational high school students in Jakarta, (3) the effect of entrepreneurship education on industrial work experience among vocational high school students in Jakarta, and (4) the effect of entrepreneurship education and industrial work experience together on entrepreneurial intentions among vocational high school students in Jakarta. This research is a quantitative study using a survey method. The population was 195 students majoring in online business and marketing at As-Sa'adah Vocational High School Jakarta, At-Taqwa Vocational High School Jakarta, and Poncol Vocational High School Jakarta who had undergone entrepreneurship learning and industrial work experience. A sample of 132 students was drawn using Proportional Random Sampling. Data collection used a questionnaire. The analysis technique used Partial Least Squares (PLS) version 4.0 for statistical analysis. The results of the study indicate that (1) Entrepreneurship education has a direct positive and significant effect on entrepreneurial intentions, (2) Entrepreneurship education has a direct positive and significant effect on industrial work practices, (3) Industrial work practices do not have a direct positive and significant effect on entrepreneurial intentions, (4) Industrial work practices do not have a direct positive and significant effect and do not act as an intervening or mediating variable between entrepreneurship education and entrepreneurial intentions.